Clarification of the katydid genus Uchuca Giglio-tos, 1898 (Orthoptera: Tettigoniidae): A new species in the Brazilian Amazon Rainforest - Tavares, Gustavo Costa; Sovano, Rafael Segtowick Da Silva; Gutjahr, Ana Lúcia Nunes (Zootaxa, 2016)
This paper accomplishes three tasks: Firstly, description of a new species, Uchuca almeirina sp. nov., from the Brazilian Amazon Rainforest, specifically from Monte Dourado, Almeirim, Pará. Secondly, it is proposed that Uchuca macroptera Montealegre-Z & Morris, 2003 be made a synonym of Uchuca ferreirai (Piza, 1976). Thirdly, a compilation of the generic distribution is presented, which includes new records of Uchuca amacayaca Montealegre-Z & Morris (2003) in Brazil and Uchuca similis Montealegre-Z & Morris (2003) in Colombia and Brazil, and the amplification of the occurrences of U. ferreirai.